BOOK REVIEW OF JANCEE DUNN’S WHY IS MY MOTHER GETTING A TATTOO - utomo, Bastian Krisnanda (LANTERN (Journal on English Language, Culture and Literature), 2015)
Communication is absolute matter that every single human in this world must have to understand one individual to other individual especially in family and public spare. Jancee Dunn wrote a novel entitled Why Is My Mother Getting a Tattoo that reveal how she communicate with many individuals with different background throughout her life. In this book review, writer intends to discuss this novel’s strengths and weaknesses. Through this book review, the writer suggest to read this novel, because through the story, the reader will study about the way to communicate with the people around.